Die waarde en funksie van liturgiese musiek - Viljoen, AM (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
The Value and Function of Liturgical Music It appears that the contribution of music in worship services is much under estimated in many church traditions. However, liturgical music should contribute towards a deeper experience of the worship service. In liturgical music, the general features of music can be applied in such a way that the liturgical moments of praise, thanksgiving, humility, confession of sins and prayers are rendered from the depths of the heart. Liturgical songs should be of a high standard. However, they should be sober to support the message of the text. Therefore, this music must complement a dignified and trustworthy expression of the contents of the words that are being sung.